Hereditary spastic paraplegia from 1880 to 2017: an historical review - Ingrid Faber; Eduardo Rafael Pereira; Alberto R. M. Martinez; Marcondes França Jr; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT The authors have constructed a brief timeline of major clinical research related to hereditary spastic paraplegia (HSP). This timeline summarizes the evolution of HSP research, from the first clinical descriptions by Adolf von Strümpell in 1880 to the present day, with the transformation of these diseases into a rapidly-growing and heterogeneous group of neurogenetic diseases.